Por uma geografia socioambiental dos municípios de Soure e Salvaterra, Marajó/Pará - Marques, Fabricia Cristian Moura de Souza (2024)
Marajó is the largest riverine-marine archipelago in the world (104,139.93 km²), divided into 16 municipalities. It presents significant contradictions analogous to the Brazilian Amazon, which remain on the margins of generational transformations in the region. Additionally, their municipalities statistics reveal a neglected population, contrasting with a territory rich in biodiversity and natural resources. The largest island in the archipelago is Marajó, covering 48,000 km². The relationships between society and nature highlight land use and occupation, usually are negligent regarding support hability from naturalresources. In this context, this work aims to analyze environmental changes resulting from socioeconomic relations in the production of space in the municipalities of Soure and Salvaterra. In these two municipalities, there are environmental systems and subsystems with invaluable geoenvironmental and landscape conditions. The integrated geoenvironmental analysis, as a theoretical-conceptual and methodological premise, enabled the identification, characterization, and delimitation of the environmental systems and subsystems that make up the two municipalities. Additionally, the application of the environmental fragility methodology allowed for the identification of the degree of fragility of the environmental subsystems in response to different modes of economic exploitation of the space, enabling the establishment of appropriate land use and occupation guidelines for Soure and Salvaterra. This approach also helps future studies in safeguarding natural resources. Understanding the socio-productive relationships and the appropriation of nature by various social actors, including the State, local governments, Secretariats, rural landowners, traditional populations, Indigenous peoples, and others, was of fundamental importance for comprehending the intense processes of environmental degradation observed. In Salvaterra, areas with Yellow Latosol and natural vegetation, cultivation areas with secondary vegetation, and low population density had an emerging weak fragility level. In contrast, areas with different types of hydromorphic soils, anthropogenic activities, and occupation along water bodies were classified as having very strong fragility. On the other hand, in Soure, the areas of very low potential fragility were those with natural herbaceous cover, pioneer formations with fluvial and lacustrine influences, low urbanization levels, and little-suppressed native vegetation, such as in flooded fields, areas with Gleysols, and non-vegetated beach areas. Similarly, in areas potentially fragile due to anthropogenic land use classes, the emerging fragility was very strong.